Clinical Efficacy and Safety of Lidocaine Tape for Topical Anesthesia of the Oral Mucosa: A Preliminary Controlled Trial - Ryouji Tani; Sachiko Yamasaki; Atsuko Hamada; Mirai Higaki; Yasuyuki Asada; Souichi Yanamoto (MDPI AG, 2023)
Local anesthesia is administered to reduce pain-induced stress during dental treatment. However, local anesthetic injections are extremely painful; thus, methods to minimize this pain should be developed. Clinical studies on the pain-relieving effects of dental topical anesthetics have shown that few topical anesthetics provide fast and adequate pain relief without harming the oral mucosa. We examined the efficacy and safety of lidocaine tape, which has a potent topical anesthetic effect. Lidocaine tape was applied to the oral mucosa of 14 healthy participants, and its suppression effect was assessed by examining the pain intensity at the non-lidocaine tape-applied site using the visual analog evaluation scale and the verbal evaluation scale. Lidocaine tape application significantly reduced visual analog scale (VAS) scores during mucosal puncture compared to non-application (p < 0.01). Moreover, lidocaine tape application significantly reduced VAS scores during local anesthetic injection compared to non-application (p < 0.001). Adverse events were evaluated using the Common Terminology Criteria for Adverse Events, version 5.0. No adverse events attributed to the application of lidocaine tape were observed in any participant. The findings in this study suggest that the application of lidocaine tape before infiltration anesthesia can reduce patient distress.